Soil microbiomes and one health - Banerjee, Samiran; van der Heijden, Marcel G A (Nature reviews. Microbiology, 2023)
The concept of one health highlights that human health is not isolated but connected to the health of animals, plants and environments. In this Review, we demonstrate that soils are a cornerstone of one health and serve as a source and reservoir of pathogens, beneficial microorganisms and the overall microbial diversity in a wide range of organisms and ecosystems. We list more than 40 soil microbiome functions that either directly or indirectly contribute to soil, plant, animal and human health. We identify microorganisms that are shared between different one health compartments and show that soil, plant and human microbiomes are perhaps more interconnected than previously thought. Our Review further evaluates soil microbial contributions to one health in the light of dysbiosis and global change and demonstrates that microbial diversity is generally positively associated with one health. Finally, we present future challenges in one health research and formulate recommendations for practice and evaluation.